Hubungan Stroke Iskemik dengan Gangguan Fungsi Kognitif di RS Universitas Sumatera Utara - Ramadhani, Salsa Shafira; Hutagalung, Haflin Soraya (SCRIPTA SCORE Scientific Medical Journal, 2020)
Background: Stroke is a major health problem worldwide, especially in Asia, which has more than 60% of the world’s population. Besides causing a health problem, stroke is also an economic and social burden in low and middle-income countries. Stroke may cause cognitive impairment, thus cognitive assessment in stroke survivors is important in addition to determine the treatment aimed at improving cognitive function following a stroke. Objectives: This study aims to determine the association between gender, age, and duration of education and cognitive impairment of post-stroke patients at Rumah Sakit Universitas Sumatera Utara. Methods: This study is an analytical research study using a cross-sectional design with a total of 24 respondents selected by consecutive sampling. Data collection was done by using medical records and interviewing the MoCA-Ina questionnaire to respondents. Results: On the analysis of chi-square obtained, gender value p = 0.673 indicating there is no association between gender and cognitive impairment, age (p = 0.035) and duration of education (p = 0.013) indicating there is an association between age as well as the duration of education and cognitive impairment of post-ischemic stroke patients. Conclusion: There is an association between age as well as the duration of education and cognitive impairment, whereas gender does not show association with cognitive impairment in post-ischemic stroke patients. Keywords: cognitive function, ischemic stroke, MoCA-Ina, post ischemic stroke Latar Belakang: Stroke merupakan masalah kesehatan utama di dunia terutama di Benua Asia dengan penduduk lebih dari 60% populasi dunia. Selain menimbulkan masalah kesehatan stroke juga menjadi beban ekonomi dan sosial di negara yang berpendapatan rendah dan menengah. Stroke dapat menyebabkan gangguan fungsi kognitif sehingga pemeriksaan fungsi kognitif pada pasien stroke merupakan hal yang penting untuk dapat menentukan penanganan selanjutnya yang bertujuan memperbaiki fungsi kognitif. Tujuan: Penelitian ini bertujuan untuk menganalisis hubungan jenis kelamin, usia dan lama pendidikan dengan gangguan fungsi kognitif pada pasien pasca stroke iskemik di Rumah Sakit Universitas Sumatera Utara. Metode: Penelitian ini merupakan penelitian analitik menggunakan desain penelitian potong lintang dengan sampel penelitian pasien pasca stroke iskemik di poliklinik saraf di Rumah Sakit Universitas Sumatera Utara dipilih dengan metode consecutive sampling sebanyak 24 responden. Pengambilan data dilakukan dengan menggunakan rekam medik serta wawancara menggunakan kuisioner MoCA-Ina kepada responden. Hasil: Pada analisis uji chi square didapatkan jenis kelamin (p = 0,673) tidak berhubungan dengan gangguan fungsi kognitif pada pasien pasca stroke, sedangkan usia (p = 0,035) dan lama pendidikan (p = 0,013) menunjukkan hubungan dengan gangguan fungsi kognitif pada pasien pasca stroke iskemik. Kesimpulan: Terdapat hubungan antara usia dan lama pendidikan dengan gangguan fungsi kognitif, sedangkan jenis kelamin tidak menunjukkan adanya hubungan dengan gangguan fungsi kognitif pada pasien pasca stroke iskemik. Kata kunci: fungsi kognitif, MoCA-Ina, pasca stroke iskemik, stroke iskemik